2022
DOI: 10.3390/cells11020190
|View full text |Cite
|
Sign up to set email alerts
|

Nephropathic Cystinosis: Pathogenic Roles of Inflammation and Potential for New Therapies

Abstract: The activation of several inflammatory pathways has recently been documented in patients and different cellular and animal models of nephropathic cystinosis. Upregulated inflammatory signals interact with many pathogenic aspects of the disease, such as enhanced oxidative stress, abnormal autophagy, inflammatory cell recruitment, enhanced cell death, and tissue fibrosis. Cysteamine, the only approved specific therapy for cystinosis, ameliorates many but not all pathogenic aspects of the disease. In the current … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 88 publications
(124 reference statements)
1
3
0
1
Order By: Relevance
“…In conclusion, our data add to the growing body of evidence demonstrating a role for inflammation in the development and progression of kidney disease in cystinosis ( 38 ). The activation of multiple inflammatory pathways and their interplay with other mechanisms involved in the pathogenesis of cystinosis, including increased oxidative stress, autophagy, mechanisms of cell death, and tissue fibrosis, have been reported ( 15 17 , 19 ).…”
Section: Discussionsupporting
confidence: 71%
“…In conclusion, our data add to the growing body of evidence demonstrating a role for inflammation in the development and progression of kidney disease in cystinosis ( 38 ). The activation of multiple inflammatory pathways and their interplay with other mechanisms involved in the pathogenesis of cystinosis, including increased oxidative stress, autophagy, mechanisms of cell death, and tissue fibrosis, have been reported ( 15 17 , 19 ).…”
Section: Discussionsupporting
confidence: 71%
“…Cysteamine is a thiol-containing compound used in the treatment of cystinosis by increasing the intracellular level of glutathione 10 11 . Studies have linked the therapeutic use of cysteamine against cystinosis with its anti-apoptotic effect 12 13 . Anti-malarial effect of cysteamine was also revealed by study of Moradin et al, 14 , and its oxidized derivative was shown to suppress sickling in sickle cell patients 15 .…”
Section: Introductionmentioning
confidence: 99%
“…A recent study from Germany showed that starting cysteamine soon after birth yielded almost normal growth and kidney function in these patients with a neonatal diagnosis [ 30 , 31 ]. Still, the availability of such strategies in low-income countries is questionable, let alone access to potential innovative therapies such as stem cell transplantation [ 32 ], or inflammation-targeted therapies [ 33 ], which are very likely to be available only in a restricted number of DEed countries.…”
Section: Discussionmentioning
confidence: 99%